Renalase levels are decreased in maternal blood and placental tissues in pregnancies associated with preterm preeclampsia - Youstina Soliman; Chino Eke; Xiaojia Guo; Melinda Wang; Tatiana Silva; Gary V. Désir; Liza Konnikova (Scientific Reports)
Abstract Preeclampsia (PEC) is a complication of pregnancy associated with hypertension and the risk of eclampsia. The pathophysiology of PEC is unknown and identifying factors associated with PEC during pregnancy is crucial for placental, fetal, and maternal health. Renalase (RNLS) is an anti-inflammatory secretory flavoprotein associated with hypertension. Recent data demonstrated a correlation between maternal serum RNLS and PEC, and work from our group identified RNLS expression in the placenta. However, it remains unknown whether RNLS levels in placenta are altered by preeclampsia. Additionally, it is unclear if there is a differential effect of preterm and term PEC on RNLS. We demonstrate that serum RNLS was reduced in preterm cases of PEC. Similarly, placental RNLS was diminished in the chorion of preterm cases of PEC. However, a reduction of RNLS in the decidua was observed with all cases of PEC, while the levels of RNLS within the placental villi were similar in all cases. Overall, we demonstrate that RNLS correlates with PEC both systemically in maternal serum and locally within the placenta, with variable effects on the different layers of the placenta and more pronounced in preterm cases.